2008
DOI: 10.1016/j.jvs.2008.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged increases in vein wall tension increase matrix metalloproteinases and decrease constriction in rat vena cava: Potential implications in varicose veins

Abstract: In rat IVC, increases in magnitude and duration of wall tension is associated with reduced contraction and overexpression of MMP-2 and -9. In light of our findings that MMP-2 and -9 promote IVC relaxation, the data suggest that protracted increases in venous pressure and wall tension increase MMPs expression, which in turn reduce venous contraction and lead to progressive venous dilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 29 publications
5
80
0
1
Order By: Relevance
“…Also, in isolated rat IVC, prolonged increases in vein wall tension are associated with decreased vein contraction and increased levels of MMP-2 and -9 in the intima and MMP-9 in the media. The decreased contraction was prevented in IVC pretreated with MMP inhibitors, supporting a role of MMPs as a link between increased venous pressure/wall tension, decreased vein contraction, and increased venous dilation (Raffetto et al, 2008). Increased venous pressure may increase venous MMP expression by inducing intermediary factors such as inflammation and hypoxia-inducible factors (HIFs).…”
Section: Venous Hydrostatic Pressure and Mmps In Vvsmentioning
confidence: 93%
See 1 more Smart Citation
“…Also, in isolated rat IVC, prolonged increases in vein wall tension are associated with decreased vein contraction and increased levels of MMP-2 and -9 in the intima and MMP-9 in the media. The decreased contraction was prevented in IVC pretreated with MMP inhibitors, supporting a role of MMPs as a link between increased venous pressure/wall tension, decreased vein contraction, and increased venous dilation (Raffetto et al, 2008). Increased venous pressure may increase venous MMP expression by inducing intermediary factors such as inflammation and hypoxia-inducible factors (HIFs).…”
Section: Venous Hydrostatic Pressure and Mmps In Vvsmentioning
confidence: 93%
“…MMPs, including MMP-1, -2, -3, -7, -8, -9, -12, -13, and MT1-MMP and MT3-MMP, are expressed in vascular cells and tissues (Chen et al, 2013). In the rat inferior vena cava (IVC), MMP-2 and -9 are localized in different layers of the venous wall, suggesting interaction with ECs, VSM, and ECM (Raffetto et al, 2008). Other studies showed MMP-1, -2, -3, and -7 in ECs and vascular smooth muscle cells (VSMCs); MMP-2 in the adventitia (Sansilvestri-Morel et al, 2007); MMP-9 in ECs, medial VSMC, and adventitial microvessels; and MMP-12 in VSMCs and fibroblasts of human great saphenous vein (Woodside et al, 2003).…”
Section: Tissue Distribution Of Mmpsmentioning
confidence: 99%
“…Such can later develop in tortuosity, buckling, varicosis, and chronic venous valvular insufficiency. [30][31][32] The substantial genetic influence of venous capacity found in our results may highlight the importance of early screening, detection, and prevention of related venous diseases in highrisk patients. Elucidation of the genes that influence venous biomechanics at different pressures and in different body positions may provide in the future important new insights into the pathophysiology of venous diseases that are associated with altered venous biomechanics.…”
Section: Discussionmentioning
confidence: 58%
“…Vein segments were stretched under 0.5 g of basal tension and allowed to equilibrate for 45 min in a water-jacketed cuvet filled with 3 ml Krebs solution bubbled with 95% O 2/5% CO2 at 37°C. Our laboratory has previously constructed the relationship between basal tension and contraction to 96 mM KCl in rat IVC and showed that 0.5-g tension produced maximal KCl contraction, and further increases in basal tension did not cause any further increases in KCl contraction (71). We also performed basal tension-KCl contraction curve on vena cavae from Preg rats and found that 0.5-g resting tension gave maximal KCl contraction, and further increases in resting tension did not cause further increases in KCl contraction.…”
Section: Animalsmentioning
confidence: 99%